Male coloration affects female gestation period and timing of fertilization in the guppy (Poecilia reticulata) - Sato, Aya; Aihara, Ryu-ichi; Karino, Kenji (PLOS ONE, 2021)
The trade-up hypothesis is a female behavioral strategy related to mating with multiple males. In this hypothesis, females can produce high-quality offspring while avoiding the risk of losing reproductive opportunities by non-selective mating with males at first mating and then re-mating with more attractive males. As an internal mechanism to realize this behavioral strategy, we predicted that females would immediately fertilize their eggs when they mated with attractive males, whereas females would delay fertilization when they mated with unattractive males to trade-up sires of offspring. The guppy (Poecilia reticulata) is an ovoviviparous fish with internal fertilization, and females show a clear mate preference based on the area of orange coloration on the bodies of males. In addition, it is known that females show a re-mating strategy consistent with the trade-up hypothesis. We tested whether the attractiveness of mated males affected the gestation period and the timing of fertilization. Females were paired with either colorful males or drab males, and the gestation periods (the number of days from mating to parturition) were compared. In addition, we dissected the abdomens of the females at intervals of several days after mating and observed whether the eggs were fertilized. The gestation period in females that were paired with attractive colorful males was significantly shorter than that in females that were paired with drab males. We found that females that mated with colorful males also had their eggs fertilized earlier than those that mated with drab males. Our findings show that differences in the timing of fertilization according to attractiveness of the mate increase the opportunity for cryptic female choice and trading up.